PENGARUH KUALITAS SUMBER DAYA MANUSIA TERHADAP PENERAPAN SAP BERBASIS AKRUAL PADA SATUAN KERJA DI WILAYAH KERJA KPPN DENPASAR - Sukadana, Ikrima Chikita; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi, 2015)
The aim of this research is to analyze the extent to which the quality of human resources affect the readiness of the application of accounting standards on the accrual-based government unit in the region of KPPN of Denpasar. Unit area in Tabanan, Gianyar, Badung, Denpasar and Bali Province is the location where this research is done. The use of tables Krecjie with a significance level of 0.05 is a guideline used to draw the sample. According to the table, the sample totaled 205 respondents. The data analysis technique used is the technique of regression analysis. The quality of human resources is statistically proven positive effect on the readiness of the application of accrualbased government accounting standards. This research also illustrates that the quality of human resources plays a very important role in the application of accounting standards on the accrual-based government unit in the region of KPPN of Denpasar.
Keywords: standar akuntansi pemerintahan, basis akrual, sumber daya manusia